Touch Me Touch-me-not: Women Plants and Healing - Shodhini and others; SHODHINI; GUPTA (Anu); CHOUDHURY (Bharati Roy); BALACHANDRAN (Indira); VINCENT (Philomena); KHANNA (Renu); NISSIM (Rina); SAROJINI (N B); BAJPAI (Smita); GANGOPADHAYA (Tanushree); MAHESHWARI(Uma) (New Delhi Kali for Women, 1997)
This compilation of over 300 plants, and review of their medicinal value, has been put together by Shodhini, a network of women's health activists that seeks to address the health needs of the most disadvantaged women. Gynaecological complaints are common, but may remain neglected for most of a woman's life. The remedies in this book are the result of five years' experience in treating women across India, for everything from vaginal discharge and menstrual disorders to pregnancy and uterine complaints, and urinary tract infections.